MODEL PUSAT PEMBELAJARAN BERBASIS TAMAN KANAK-KANAK UNTUK KESIAPAN KELOMPOK BERMAIN - Amelia, R.A; Wulandari, Retno (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2022)
This study aims to identify playgroup kindergartens based on the learning center model and to find out how teachers provide incentives during learning activities. This research was conducted in the mother-child group of grade 15 children. This study used a phenomenological qualitative research methodology. Data analysis uses the Miles and Huberman model as steps for (1) data reduction, (2) data presentation, and (3) inference and validation. Data collection was carried out through observation, interviews, and the use of the NST test to measure children's school readiness. The results of this study suggest the existence of play groups. The stimulation provided by the teacher from morning to noon through habituation activities.